The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0100-69912008000500008
|View full text |Cite
|
Sign up to set email alerts
|

Influência de válvulas artificiais sobre a morfometria intestinal de ratos

Abstract: ; Floripes Maria Cardoso Rossman 6 RESUMO: Objetivo: Avaliar o papel de válvulas artificiais constituídas por seromiotomias circunferenciais duplas no comprimento dos vilos, no diâmetro do intestino delgado e no peso de ratos. Método: Foram utilizados 40 ratos, distribuídos em quatro grupos. Os animais do Grupo R foram submetidos à ressecção de 50% do intestino delgado, sem criação de válvulas. No Grupo RV associaram duas válvulas à ressecção intestinal. No Grupo V foram criadas duas válvulas, sem ressecção in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
1
Order By: Relevance
“…The creation of sphincter mechanisms in the small intestine is related to the control of intestinal transit speed, particularly in bowel resections. Studies in rats, dogs and humans has shown that artificial valves slow intestinal transit and promote weight gain after intestinal resections 18,[23][24][25][26] . Besides these results, some described techniques show reduction of colonization of the proximal segments of the small intestine through the identification of bacterial growth by intraluminal collections or stool culture.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The creation of sphincter mechanisms in the small intestine is related to the control of intestinal transit speed, particularly in bowel resections. Studies in rats, dogs and humans has shown that artificial valves slow intestinal transit and promote weight gain after intestinal resections 18,[23][24][25][26] . Besides these results, some described techniques show reduction of colonization of the proximal segments of the small intestine through the identification of bacterial growth by intraluminal collections or stool culture.…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Os critérios utilizados pelos investigadores para classificação de um paciente como portador de síndrome do intestino curto são muito variáveis. De acordo com guidelines publicados pela American Gastroenterology Association (AGA, 2003) (FELDMAN et al, 1976;MARCHINI et al, 1996;STURM et al, 1997;FURTADO, 2008). O fator luminal, caracterizado pela presença de nutrientes na luz intestinal, é essencial no processo de adaptação intestinal, pois a hiperplasia adaptativa da mucosa intestinal somente ocorre se os nutrientes estiverem presentes no lúmen intestinal (ASPEN, 2005).…”
Section: I22 Síndrome Do Intestino Curtounclassified